PENGARUH PERENCANAAN DANA DESA TERHADAP KEBERHASILAN PROGRAM DANA DESA DENGAN GOOD GOVERNANCE SEBAGAI VARIABEL INTERVENING DI DESA ASINAN KECAMATAN BAWEN KABUPATEN SEMARANG - Pandi Afandi (Prosiding Seminar Nasional Akuntansi dan Manajemen (SENAMA), 2018)
This research aims to analyze village fund plan which is managed by village apparatus with  good village government management (good governance) to support the success of village fund program in empowering villagers. Sample retrieval technique in this research is non probability sampling with a kind of sensus sample, that is 23 respondents which is consist of village apparatus and member of BPD in Asinan village Bawen District Semarang Regency. Data analysis in this research uses regression analysis and path analysis. The result of this research shows that village fund plan has a positive impact toward good governance, and good governance has a positive impact toward the success of village fund program.Path analysis result shows that village fund plan has a direct effect toward success of village fund program in empowering society without uses good governance as intervening variable. A comprehension of village apparatus about village fund management which is appropriate with rule of low must be continuously socialized to avoid problems that may occur later in the future in village fund management.